“Beauty Is How You Feel Inside”: Aesthetic Judgments Are Related to Emotional Responses to Contemporary Music - Egermann, Hauke; Reuben, Federico (Frontiers in Psychology, 2020)
While it has extensively been argued that aesthetic categories such as beauty have a direct relationship to emotion, there has only been limited psychological research on the relationship between aesthetic judgments and emotional responses to art. Music is recognized to be an art form that elicits strong emotional responses in listeners and it is therefore pertinent to study empirically how aesthetic judgments relate to emotional responses to music listening. The aim of the presented study is to test for the impact of aesthetic judgment on various psychophysiological response measures of emotion that were assessed in parallel in two contemporary music concerts, each with a different audience and program. In order to induce different levels of aesthetic judgments in participants, we assigned them randomly to one of two groups in a between-subjects design in both concerts: One group attended a talk on the music presented, illustrating its aesthetic value, while the other group attended an unrelated talk on a non-musical topic. During the concerts, we assessed, from 41 participants in Concert 1 (10 males; mean age 23 years) and 53 in Concert 2 (14 males; mean age 24 years), different emotional response components: (a) retrospective rating of emotion; (b) activation of the peripheral nervous system (skin conductance and heart rate); (c) the activity of two facial muscles associated with emotional valence (only Concert 1). Participants listened to live performances of a selection of contemporary music pieces. After each piece, participants rated the music according to a list of commonly discussed aesthetic judgment criteria, all thought to contribute to the perceived aesthetic value of art. While preconcert talks did not significantly impact value judgment ratings, through factor analyses it was found that aesthetic judgments could be grouped into several underlying dimensions representing analytical, semantic, traditional aesthetic, and typicality values. All dimensions where then subsequently shown to be related to subjective and physiological responses to music. The findings reported in this study contribute to understanding the relationship between aesthetic judgment processes and emotional responses to music. The results give further evidence that cognitive-affective interactions have a significant role in processing music stimuli.